Peran Guru dalam Praktek Kegiatan Keagamaan Terhadap Perkembangan Moral Anak di TK IT Al-Anwar Kota Bengkulu - Wahyuni, Sri; Andani, Fidhia (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to analyze the role of teachers in the implementation of religious activities in relation to the moral development of children at TK IT Al-Anwar, Bengkulu City. The method used is qualitative research with a case study approach, which includes in-depth interviews, observation, and document analysis. The results show that teachers play an important role in instilling religious values through routine activities such as religious education, joint prayers, and social activities. These activities not only enrich the children's religious knowledge but also shape their character and morality. The findings emphasize the importance of teachers as role models and guides in developing positive attitudes and ethical behavior in children.